Alfred Valdmanis and the politics of survival - Bassler, Gerhard P., 1937- (desLibris. Books collection., 2000)
"Valdmanis's wily political manoeuvring is more the stuff of fiction than history. Between 1938, at age 29, and his ironic downfall in the safe haven of Canada, he was a finance minister of pre-war Latvia, a government official during the Soviet invasion, a shrewd collaborator under the Nazi occupation, then, a friend to the Allies, a spokesman for Latvian POW and displaced persons, and an adviser to the government of Canada